2006
DOI: 10.1203/01.pdr.0000246072.04663.bb
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Aromatase, Estrogen Receptor α and β, Androgen Receptor, and Cytochrome P-450scc in the Human Early Prepubertal Testis

Abstract: ABSTRACT:The expression of aromatase, estrogen receptor ␣ (ER␣) and ␤ (ER␤), androgen receptor (AR), and cytochrome P-450 side chain cleavage enzyme (cP450 scc ) was studied in prepubertal testis. Samples were divided in three age groups (GRs): GR1, newborns (1-to 21-d-old neonates, n ϭ 5); GR2, postnatal activation stage (1-to 7-mo-old infants, n ϭ 6); GR3, childhood (12-to 60-mo-old boys, n ϭ 4). Absent or very poor detection of ER␣ by immunohistochemistry in all cells and by mRNA expression was observed. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 33 publications
5
57
0
3
Order By: Relevance
“…In the present study, the immunolocalization of AR in nuclei of Sertoli cells, myoid and Leydig cells of testis from control and experimental rats was in agreement with many previous studies [13,16,[29][30][31]. However, we also found the cytoplasm of spermatogonia and spermatocytes in III/IV stages of the seminiferous epithelium cycle in testis of experimental rats was AR-immunopositive, while the cytoplasm of germ cells of other stages of the seminiferous epithelium cycle was immunonegative.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the immunolocalization of AR in nuclei of Sertoli cells, myoid and Leydig cells of testis from control and experimental rats was in agreement with many previous studies [13,16,[29][30][31]. However, we also found the cytoplasm of spermatogonia and spermatocytes in III/IV stages of the seminiferous epithelium cycle in testis of experimental rats was AR-immunopositive, while the cytoplasm of germ cells of other stages of the seminiferous epithelium cycle was immunonegative.…”
Section: Discussionsupporting
confidence: 93%
“…During the neonatal period in testicular specimens obtained from boys aged between 1 and 21 d, aromatase has been immunolocalized in both Leydig and germ cells with inconsistent staining in Sertoli cells across patient samples. 33 The same study also showed that aromatase immunolocalization between 1 mo and 5 y of age in germ and Sertoli cells is consistent with the neonatal results, however between 1 and 7 mo of age, the intensity of Leydig cell immunoreactivty decreases and between 1 and 5 y the Leydig cell aromatase immunoreactivity is absent. 33 In contrast, another study has claimed that at 3 and 8 mo of age no aromatase immunoreactivity is present in any testicular cell type.…”
supporting
confidence: 68%
“…In humans, ESR2, but not ESR1 and androgen receptor (AR), is expressed in gonocytes and spermatogonia (29). It is worth to mention that ESR2 is coexpressed with ESR1 in tumoral seminoma cells, where it may counteract the tumor cell proliferation mediated by ESR1 (30).…”
Section: Testismentioning
confidence: 99%